Therapeutic effect of mitoxantrone combined with methylprednisolone in multiple sclerosis: a randomised multicentre study of active disease using MRI and clinical criteria. Issue 2 (February 1997) - Edan, G; Miller, D; Clanet, M; Confavreux, C; Lyon-Caen, O; Lubetzki, C; Brochet, B; Berry, I; Rolland, Y; Froment, J C; Cabanis, E; Iba-Zizen, M T; et al.
Abstract : OBJECTIVE: To evaluate the efficiency of mitoxantrone in multiple sclerosis. METHODS: Forty two patients with confirmed multiple sclerosis, selected as having a very active disease on clinical and MRI criteria were randomised to receive either mitoxantrone (20 mg intravenously (IV) monthly) and methylprednisolone (1 g iv monthly) or methylprednisolone alone over six months. In the steroid alone group five patients dropped out due to severe exacerbation. RESULTS: Blinded analysis of MRI data showed significantly more patients with no new enhancing lesions in the mitoxantrone group compared with the steroid alone group, (90% v 31%, P < 0.001). In the mitoxantrone group there was a month by month decrease almost to zero in the number of new enhancing lesions, and in the total number of enhancing lesions, whereas both remained high in the steroid alone group. The differences were significant for both indices at all months from 1-6. Unblinded clinical assessments showed a significant improvement in change in EDSS at months 2-6 in the mitoxantrone group, with a final mean improvement of more than one point (-1.1 v + 0.3; P < 0.001). There was a significant reduction in the number of relapses (7 v 31; P < 0.01), and an increase in the number of patients free of exacerbation (14 v 7; P < 0.05). CONCLUSION: In this selected group of patients with multiple sclerosis with very active disease, mitoxantrone combined with methylprednisolone was effective in improving both clinical and MRI indices of disease activity over a period of six months whereas methylprednisolone alone was not. Further double blinded long term studies are needed to properly evaluate the effect of mitoxantrone on progression in disability.